2012
DOI: 10.1016/j.jcgg.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for frequent emergency department visits of veterans home residents in Northern Taiwan

Abstract: a b s t r a c tPurpose: The purpose of this study was to evaluate risk factors for frequent emergency department (ED) visits among older Chinese men living in a veterans home in northern Taiwan Methods: In 2006, all residents of Banciao Veterans Home were invited for study. Minimum Data Set Nursing Home 2.1 Chinese version, Chinese version of Geriatric Depression Scale (GDS) short form, minimental status examinations (MMSE), and Charlson Comorbidity Index (CCI) were used for study. ED records of all study part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…It has been reported that depressive symptoms as a result of acute or chronic conditions might be improved by PAC services due to increased social interactions between patients, clinical staff and caregivers, which might explain the lack of association between GDS score and acute ward readmissions in the present study. Although acute hospitalizations and critical care can jeopardize cognitive function in older patients, the associations between the cognitive decline and acute ward readmissions remains controversial . Nevertheless, low MMSE score at PAC unit admission was the only predictive factor of medical ward readmissions in the present study.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…It has been reported that depressive symptoms as a result of acute or chronic conditions might be improved by PAC services due to increased social interactions between patients, clinical staff and caregivers, which might explain the lack of association between GDS score and acute ward readmissions in the present study. Although acute hospitalizations and critical care can jeopardize cognitive function in older patients, the associations between the cognitive decline and acute ward readmissions remains controversial . Nevertheless, low MMSE score at PAC unit admission was the only predictive factor of medical ward readmissions in the present study.…”
Section: Discussionmentioning
confidence: 47%
“…Although acute hospitalizations and critical care can jeopardize cognitive function in older patients, 39 the associations between the cognitive decline and acute ward readmissions remains controversial. [40][41][42] Nevertheless, low MMSE score at PAC unit admission was the only predictive factor of medical ward readmissions in the present study. Among all patients readmitted to acute wards, the vast majority were due to acute medical conditions, but surgical conditions all occurred in late readmissions.…”
Section: Discussionmentioning
confidence: 82%
“…17 The increased transport rates for people with multiple chronic diseases and people with chronic cardiac conditions are consistent with studies from in-hospital settings where these are associated with increased risk of ED presentation. 4,18,19 Additionally, across inpatient settings, chronic mental illness has also been associated with increased rate of emergency health system use and supports the higher rate of transport for patients with a diagnosis of depression. 20 Studies from hospital settings have produced varying results regarding the impact of cognitive impairment and dementia on presentation to hospital, with some reporting increased and some reporting decreased presentation rates in these groups.…”
Section: Discussionmentioning
confidence: 92%
“…20 Studies from hospital settings have produced varying results regarding the impact of cognitive impairment and dementia on presentation to hospital, with some reporting increased and some reporting decreased presentation rates in these groups. 4,[18][19][20][21] This variation may reflect unmeasured differences in resources of RACs such as specialist dementia care units, availability of outreach and community care services and prevalence of advance care directives between different study settings. 4 In our study, there was no significant association between dementia and odds of transport to hospital.…”
Section: Discussionmentioning
confidence: 99%
“…All residents living in the Gangshan Veterans Home, a veterans retirement community in southern Taiwan, were invited to participate in the study and were screened for study enrolment if informed consent was obtained. Of the 389 residents being screened, one woman and 11 people aged younger than 65 years were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%